Serum, liver and bile sitosterol and sitostanol in obese patients with and without NAFLD. Issue 2 (20th April 2018) - Tauriainen, Milla-Maria; Männistö, Ville; Kaminska, Dorota; Vaittinen, Maija; Kärjä, Vesa; Käkelä, Pirjo; Venesmaa, Sari; Gylling, Helena; Pihlajamäki, Jussi
Abstract : Background and aims : Non-alcoholic fatty liver disease (NAFLD) associates with low levels of serum plant sterols in cross-sectional studies. In addition, it has been suggested that the hepatic sterol transport mechanisms are altered in NAFLD. Therefore, we investigated the association between serum, liver and bile plant sterols and sitostanol with NAFLD. Methods : Out of the 138 individuals (age: 46.3 ± 8.9, body mass index: 43.3 ± 6.9 kg/m², 28% men and 72% women), 44 could be histologically categorized to have normal liver, and 94 to have NAFLD. Within the NAFLD group, 28 had simple steatosis and 27 had non-alcoholic steatohepatitis. Plant sterols and sitostanol were measured from serum ( n =138), liver ( n =38), and bile ( n =41). The mRNA expression of genes regulating liver sterol metabolism and inflammation was measured ( n =102). Results : Liver and bile sitostanol ratios to cholesterol were higher in those with NAFLD compared to those with histologically normal liver (all P <0.022). Furthermore, liver sitostanol to cholesterol ratio correlated positively with histological steatosis and lobular inflammation ( r s > 0.407, P <0.01 for both). In contrast, liver sitosterol to cholesterol ratio correlated negatively with steatosis ( r s = −0.392, P =0.015) and lobular inflammation ( r s = −0.395, P =0.014). Transcriptomics analysis revealed suggestive correlations between serum plant sterol levels and mRNA expression. Conclusion : Our study showed that liver and bile sitostanol ratios to cholesterol associated positively and liver sitosterol ratio to cholesterol associated negatively with liver steatosis and inflammation in obese individuals with NAFLD..